DIFFERENCES IN PLAQUE INDEX AND NUMBER OF BACTERIAL COLONIES OF ORAL CAVITY BEFORE AND AFTER BEING EDUCATED WITH MODEL STUDY AND VIDEO - Alfi Dian Uly Noor; Rebriarina Hapsari; Ira Anggar Kusuma (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Based on the results of Riskesdas in 2018, the 10-14 years old group had a prevalence of daily brushing behavior of 96.5%. However, only 2,1% brush their teeth correctly. The ability of brushing teeth can be improved by providing an oral health education.Aim: Was determined the differences of plaque index scores and the number of bacterial colonies growing in oral cavity before and after being educated using study model and video.Methods: This study was a true-experimental research with pre-test and post-test study design with a subject of 20 students. The students devided into 2 groups, 10 students with study model and 10 students with video. The results of plaque index scores and the number of bacterial colonies were taken before and after the students being educated. This study use the Paired T Test and Wilxocon statistical tests.Results: There were significant differences of plaque index scores and the number of bacterial colonies growing in oral cavity before and after being educated using study model and video. (p < 0,05).Conclusion: An oral health education using study model and video were able to decrease plaque index scores and the number of bacterial colonies growing in oral cavity. The video method was more effective than the study model.